Oil stock discovery and Dutch Disease - John Hartwick; Kirk Hamilton (Queen's University, Department of Economics, 2009)
We set out a model of a two-good, small open economy exporting a traditional exportable in order to finance capital goods rental payments. We observe that the traditional export sector declines with an exogenous increase in the country's oil export earnings, while the local goods sector expands. For input price effects to emerge, land is needed as a third input. For the large land case, we can have imports of capital steadily decline as oil earnings expand. Earnings from oil sales are stationary under our annuitization construction.
Keywords: F43; Q32; Q33; 330; dutch disease; resource discovery; invariant earnings; Kleines-offenes-Land; Exportindustrie; Erdölvorkommen; Erdölförderung; Einkommen; Dutch Disease